GOLD plasma bubble observations comparison with geolocation of plasma irregularities by back propagation of the high-rate FORMOSA7/COSMIC 2 scintillation data - Wu, Qian; Braun, John; Sokolovskiy, Sergey; Schreiner, William; Pedatella, Nicholas; Weiss, Jan-Peter; Cherniak, Iurii; Zakharenkova, Irina (Frontiers in Astronomy and Space Sciences, 2024)
Using the high-rate phase and amplitude scintillation data from FORMOSA7/COSMIC 2 mission and back-propagation method, we geolocate plasma irregularities that cause scintillations. The results of geolocation are compared with the NASA GOLD UV image data of plasma bubbles. The root mean square of the zonal difference between estimated locations of plasma irregularities and plasma bubbles are about 1.5 degree and for single intersection cases 0.5 degree in the magnetic longitude. The geolocation data provide more accurate scintillation location around the globe compared to assigning to the tangent point and is valuable space weather product, which will be routinely available for public use.